Chronic Periodontitis Is Associated With Spinal Dysmobility in Patients With Ankylosing Spondylitis. Issue 12 (1st December 2015) - Kang, Eun Ha; Lee, Jung Tae; Lee, Hyo‐Jung; Lee, Joo Youn; Chang, Sung Hae; Cho, Hyon Joung; Choi, Byoong Yong; Ha, You‐Jung; Park, Kyoung Un; Song, Yeong Wook; Van Dyke, Thomas E.; Lee, Yun Jong
Abstract : Background: Although microbes have been suggested to play a role in the pathogenesis of ankylosing spondylitis (AS), several studies present contradictory results regarding the association between AS and chronic periodontitis (CP). Methods: Clinical, laboratory, and medication data were collected from 84 patients with AS and 84 age‐ and sex‐matched controls. Periodontal measurements, including probing depths (PDs), clinical attachment loss (AL), serum anti‐ Porphyromonas gingivalis titers, and the detection of P. gingivalis DNA in gingival crevicular fluid, were recorded. All participants with periodontitis with PD ≥4 to <7 mm received scaling and root planing and were re‐evaluated at 12 weeks; those still exhibiting periodontitis with PD of ≥4 to <7 mm at 12 weeks were followed at 24 weeks. Results: The prevalence of moderate‐to‐severe CP was not different between patients with AS and controls (70.2% versus 66.6%). The P. gingivalis detection rate was not different between patients with AS and controls or between patients with AS receiving and not receiving anti–tumor necrosis factor (TNF)‐α agents. However, CP was positively associated with impaired spinal mobility of patients with AS in multivariate analyses. After periodontal treatment, PD and AL levels were improved in both groups, but the change was significantly greater in patients with AS than in controls. Patients with AS receiving anti‐TNF‐α agents exhibited a greater improvement in PD and AL than those who did not. Conclusions: Although AS was not associated with the presence of CP, CP was associated positively with the severity of spinal dysmobility in Korean patients with AS. These results suggest that periodontitis can have a negative effect on axial movement in AS.